High-performance sport management in Latvia: a review of athletes' view - Dombrovska, A.; Luika, S.; Abolins, V. (LASE Journal of Sport Science, 2017)
Countries around the world invest an increasingly larger number of resources into sport, especially in a high-performance sport with an aim to achieve success. High-performance development systems and programs result in international success. A gap may arise between goals and tasks defined in documents and implemented in real-time. Some features can be subjectively assessed by their primary users, in this case - high-performance athletes. The consequence may be dissatisfaction, which can affect athletes` performance. Therefore, this study aims to get a better understanding of the high-performance sport management in Latvia from the high-performance athletes` view. Research methods are as follows: analysis of scientific literature and other studies, questionnaire, and statistical analysis. High-performance athletes were contacted to complete an online survey related to theory and this question. 156 high-performance athletes completed the questionnaire. The ability to properly understand the situation of the sports management in Latvia gives sport directors the opportunity to manage and develop the high-performance sport more effectively by taking into the account athletes` view. The most important finding of this analysis is that there are a lot of issues for potential improvement in the high-performance sport management in Latvia.